A Pharmacist-Driven Education and Intervention Program that Improves Outcomes for Hypertensive Patients - Alicia Zagel; Adam Rhodes; Jeri Nowak; Amanda Brummel (University of Minnesota Libraries Publishing, 2022)
Purpose: Uncontrolled hypertension is serious and may lead to severe cardiovascular events and death. To better educate and empower patients to meet their blood pressure (BP) management goals, a large, integrated academic healthcare system implemented the Blood Pressure Goals Achievement Program (BPGAP), a longitudinal intervention embedding community pharmacists within healthcare teams. This study evaluated BPGAP on its ability to promote patient BP management goals. Methods: A pre-/post-intervention analysis was conducted whereby BP measurements were evaluated longitudinally within acuity groups determined by k-means clustering. Generalized linear mixed models evaluated trends in BP by time period, and proportions of patients meeting BP management goals (<140/90 mmHg) were assessed in relation to BPGAP enrollment date. Results: There were 5,125 patients who were clustered into Uncontrolled, Borderline, and Controlled blood pressure groups; 2,108 patients had BP measurements across 4 time periods before and after BPGAP enrollment. Groups differed by patient age, sex, and other demographics (p<0.0001). Patients in the Uncontrolled and Borderline BP clusters demonstrated significant BP decreases after BPGAP enrollment, continuing at least to 1-year post-intervention; Controlled cluster patients maintained BPs throughout the study period. The proportion of patients with controlled BPs increased from 56% immediately pre-BPGAP to 74% in the 3- to 6-months following enrollment. Conclusion: BPGAP is effective at helping patients achieve their BP management goals. Pharmacists may play a key role in hypertension control through measuring BPs and including updates and recommendations in the electronic health record, educating patients, and engaging in communication with healthcare teams.